Prospecção, caracterização e purificação de lipase microbiana - Gama, Auricelia Matos da (2012)
Lipases are enzymes which catalyze the synthesis and hydrolysis of glycerides in triacylglycerols and fatty acids. Its use as a biological catalyst has taken various applications in the pharmaceutical and food industries. Your source may be either animal, plant and microbial. With great emphasis on the latter due to the advantages as a means of obtaining, handling and great diversity, which makes filamentous fungi an interesting source of lipases. The search for new sources provides several jobs with specific objectives. Thus the aim of this study was to evaluate and select among two collections of filamentous fungi, potential producers of lipases. For this study, 316 strains were actually tested for lipolytic activity in liquid culture medium inducing lipase (olive oil). Of this total, 298 (94%) were positive and their lipase activity observed from the hydrolysis reaction with the substrate p-NPP with reading in the spectrophotometer at 410 nm. Only isolates exhibiting activity above 7000 U / ml were selected. Thus, only six isolates showed activities considered good and underwent further testing with enzyme activity in palm oil. The most promising strain was identified through molecular techniques as Endomelanconiopsis endophytica, producing an activity of 7895 U/mL for the olive oil and 10,727 U/mL for palm oil. The crude extract was then purified by ion exchange chromatography, resulting in three enzymes active form (two of 60 and one of 46 kDa) quantified by SDS-PAGE. And their identity verified by mass spectral and N-terminal sequencing by Edmann degradation. Two of them were presented blocked and the 46 kDa its sequence was obtained. Thus the study sought to contribute to the discovery of new lipases with biotechnological potential, contributing to a future database protein. Keywords: lipases, filamentous fungi, submerged fermentation, purification